Digital Competency in Teaching and Learning of Building Construction Malaysian Skills Certificate - MOHAMAD, MIMI MOHAFFYZA; Abd Rahman, Aqmal Redza (Research and Innovation in Technical and Vocational Education and Training, 2023)
Nowadays, the digital teaching and learning approach is familiar in education. The need to provide digital teaching materials requires dynamic teacher competence. The TVET field is also no exception to this requirement. This study consists of three main objectives: identifying the competence of online teaching material development among teaching staff, the competence of online teaching delivery, and the implementation of the online assessment. Therefore, this study aimed to examine digital competence in implementing the teaching and learning of the Malaysian Skills Certificate in the construction field. The survey research design with a quantitative approach implements in this study. A questionnaire was distributed to Vocational Colleges and Accredited Centre for Malaysia Skills Certificate in Building Construction. There are thirty respondents’ responses to the questionnaire. The result shows identifying the competence in developing online teaching materials among employees with a mean value of 4.55, in contrast, determining the competence of online teaching delivery among teaching staff with a mean value of 4.38. In addition, identify how the teaching staff implements the online assessment with a mean score of 4.45. Therefore, this shows that digital competence in the implementation of teaching and learning Malaysian Skills Certificate is at a high level in the construction field. The ability of digital teaching and learning that is not directly face-to-face with students no longer needs to be doubted. Undoubtedly, digital teaching and learning can improve student performance better than face-to-face learning and produce quality graduates. In conclusion, digital competency requires preparing and implementing TVET teaching, and the teaching staff is aware of the new paradigm shift in TVET’s pedagogical approach.